2022
DOI: 10.1002/cac2.12256
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific effectiveness of primary human papillomavirus screening versus cytology in a cervical cancer screening program: a nationwide cross‐sectional study

Abstract: Background Primary human papillomavirus (HPV) screening is recommended for the detection of cervical intraepithelial neoplasia (CIN) in the general population; however, the triage for HPV‐positive women remains a challenge. This study aimed to evaluate the age‐specific effectiveness of primary HPV screening versus primary cytology screening for identifying optimal strategies for women of different ages. Methods The dataset of the prevalence round screening was derived from the National Cervical Cancer Screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…However, the prevention and treatment of cervical cancer in China has not obtained promising results, and cervical cancer has become prevalent in young people [26,27]. Globally, young women (< 25 years of age) are prone to peak HPV infection rates, whereas a second peak in older women has been observed in regions such as China, East Africa and Latin America [28][29][30]. A second peak in invasive cancers used to be seen (in the UK) in the early 1990s, but this has largely disappeared as screening has detected and treated much of the CIN in younger women.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevention and treatment of cervical cancer in China has not obtained promising results, and cervical cancer has become prevalent in young people [26,27]. Globally, young women (< 25 years of age) are prone to peak HPV infection rates, whereas a second peak in older women has been observed in regions such as China, East Africa and Latin America [28][29][30]. A second peak in invasive cancers used to be seen (in the UK) in the early 1990s, but this has largely disappeared as screening has detected and treated much of the CIN in younger women.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Chongqing Hospital reported that among 1,055 participants, 211 cases were ≥cervical intraepithelial neoplasia 2 (CIN2), resulting in a detection rate of 20% ( 4 ). Previous studies have reported that the detection of CIN and ICC ranged from 4.1 to 6.0 per 1,000 in different age groups with different cervical cancer screening methods in the general population ( 5 ). In hospitals, most patients had abnormal cervical screening results, making them a high-risk population, thus the detection rate of cervical cancer was much higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Second, longitudinal follow-up should be carried out in women with both negative LBC and AHPV results. Finally, the performance of primary HPV screening with different triage strategies differed among age groups ( Bao et al., 2022 ). Evaluation of the age-specific effectiveness of primary AHPV screening and possible triage strategies is warranted.…”
Section: Discussionmentioning
confidence: 99%